PRESCRIPTION PROFILE OF ANTIHYPERTENSIVE DRUGS IN PREECLAMPSIA PATIENTS AT KIRANA HOSPITAL - Lubada, Eziah Ika; Fandinata, Selly Septi; Alfiana, Silvina Sita; Suryandari, Mercyska; Isdianto, Andik (International Islamic Medicine Forum, 2024)
Preeclampsia is a complication of pregnancy with symptoms of hypertension ≥ 140/90 mmHg and proteinuria ≥ 0.3 grams/24 hours or 30 mg/dl (+1 dipstick) arising after more than 20 weeks of gestation in previously normotensive pregnant women. Maternal deaths in Indonesia in 2021 related to hypertension in pregnancy reached 1077 cases (Source: Directorate General of Public Health, Ministry of Health, 2021). Pharmacological therapy intervention, antihypertensive treatment is also needed in addition to maintaining a healthy lifestyle. The purpose of the study was to determine the description of pharmacological therapy including the pharmacological class of drugs, drug names, drug doses, rules of use, and types of antihypertensive drug therapy (single / combination) in patients with preeclampsia. This type of descriptive observational research is retrospective with total sampling obtained from medical records and patient prescriptions. The results of this study were the incidence of preeclampsia aged 35 years and over by 21 patients (36%) and the most common diagnosis was mild preeclampsia by 38 samples (66%). The use of nifedipine which is included in the CCB (Calcium Channel Blocker) group was 42 respondents (72%). Meanwhile, the use of methyldopa which is included in the central sympatholytic group was 17 respondents (28%). In the single therapy type study, 59 prescriptions (100%) used nifedipine or methyldopa. Pregnant women are encouraged to routinely conduct antenatal care checks at the hospital every month.